A new asymmetric phthalocyanine-based chemosensor for the detection of ultra trace amount of copper (II) ions in environmental samples: comprehensive complex characterization and DFT analysis - Yavuz, Ozgur; Yildiz, Burak; Ahmetali, Erem; Aribuga, Hulya; Ertugral, Utku; Kura, Berkehan; Tuzun, Nurcan Senyurt; Sener, M. Kasim; Yilmaz, Ismail (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
While Cu2+ ions are essential for various biological and physiological processes, they can also induce severe neurodegenerative disorders, such as Alzheimer's and Parkinson's disease, when present in excess. Therefore, there is a pressing need to develop novel chemical sensors capable of selectively and sensitively detecting these ions in environmental samples. In this study, an A3B-type asymmetric phthalocyanine-based sensor, PCA-ZnPc-5, was developed by integrating tert-butyl groups and pyrazole moieties. These units play an active role in suppressing aggregation and increasing the solubility of the sensor molecule, as well as functioning as selective receptors against Cu2+, respectively. PCA-ZnPc-5 facilitated the detection of Cu2+ ions at the nanomolar level in environmental matrices, with no interference from other species. The applied fluorescence-based method yielded in a detection limit of 7.38 nM and an ultra-fast response time of one second. A notably significant binding constant of 4.89 x 106 M-1 confirmed the strong interaction between PCA-ZnPc-5 and Cu2+. The recovery percentages ranged from 97.9 % to 102.9 %, indicating the efficacy and suitability of PCA-ZnPc-5 for the analysis of Cu2+ in actual samples. The binding stoichiometry (1:1 ratio) and mechanism were confirmed by a comprehensive analytical approach including UV-Vis, FT-IR, MALDI-TOF Spectroscopy, and Job's Method. The 3-dimensional geometries of the probe and its Cu2+ complex were elucidated through DFT calculations, which also revealed the binding mode and the frontier molecular orbitals of the system.
Keywords: Asymmetric phthalocyanine; Pyrazole; Near-infrared probe; Copper (II) determination; Density functional theory; FLUORESCENT; SPECTROMETRY; CU(II); SENSOR; CO; CU; Spectroscopy